Bovine Coronavirus Co-infection and Molecular Characterization in Dairy Calves With or Without Clinical Respiratory Disease - Frucchi, Ana Paula S.; Dall Agnol, Alais M.; Bronkhorst, Dalton E.; Beuttemmuller, Edsel A.; Alfieri, Amauri A.; Alfieri, Alice F. (Frontiers in Veterinary Science, 2022)
Bovine respiratory disease (BRD) is considered a major cause of morbidity and mortality in young calves and is caused by a range of infectious agents, including viruses and bacteria. This study aimed to determine the frequency of viral and bacterial pathogens detected in calves with BRD from high-production dairy cattle herds and to perform the molecular characterization of N and S1 genes in identified bovine coronavirus (BCoV) strains. Nasal swabs were collected from 166 heifer calves, namely, 85 symptomatic and 81 asymptomatic calves aged between 5 and 90 days, from 10 dairy cattle herds. Nasal swabs were evaluated using molecular techniques for the identification of viruses (BCoV, bovine alphaherpesvirus 1, bovine viral diarrhea virus, bovine parainfluenza virus 3, and bovine respiratory syncytial virus) and bacteria (Pasteurella multocida, Mannheimia haemolytica, Histophilus somni, and Mycoplasma bovis). In addition, five and two BCoV-positive samples were submitted to N and S1 gene amplification and nucleotide sequencing, respectively. The frequency of diagnosis of BCoV was higher (56%, 93/166) than the frequency of P. multocida (39.8%, 66/166) and M. haemolytica (33.1%, 55/166). The three microorganisms were identified in the calves of symptomatic and asymptomatic heifer calve groups. All other pathogens included in the analyses were negative. In the phylogenetic analysis of the S1 gene, the Brazilian strains formed a new branch, suggesting a new genotype, called # 15; from the N gene, the strains identified here belonged to cluster II. This study describes high rates of BCoV, P. multocida, and M. haemolytica in heifer calves from high-production dairy cattle herds with BRD. Additionally, the molecular characterization provides evidence that the circulating BCoV strains are ancestrally different from the prototype vaccine strains and even different BCoV strains previously described in Brazil.